To resolve a pair the equations making use of substitution, an initial solve among the equations for among the variables. Climate substitute the an outcome for that variable in the various other equation.

You are watching: (3x^3/2y^3/x^2y^-1/2)^-2

select one the the equations and also solve it for x by isolating x top top the left hand side of the equal sign.
substitute 1 because that y in x=3y-1. Due to the fact that the result equation includes only one variable, you can solve for x directly.
2x+y=3;x-2y=-1 Solution : x,y = 1,1 device of linear Equations entered : <1> 2x + y = 3 <2> x - 2y = -1 Graphic depiction of the Equations : y + 2x = 3 -2y + x = -1 solve by Substitution ...
displaystyleleft(x=frac407,y=-frac247 ight. Explanation: displaystyle2x+y=8, ext Eqn (1)displaystyle3x-2y=24, ext Eqn (2)displaystyle4x+2y=16, ext Eqn(1) * 2 ...
3(4xy-12y+6yz)+3 Final result : 3 • (4xy + 6yz - 12y + 1) step by action solution : step 1 : action 2 :Pulling out prefer terms : 2.1 traction out favor factors : 4xy - 12y + 6yz = 2y • (2x + 3z ...
2x+y=4;3x-2y=-1 Solution : x,y = 1,2 system of linear Equations entered : <1> 2x + y = 4 <2> 3x - 2y = -1 Graphic representation of the Equations : y + 2x = 4 -2y + 3x = -1 fix by ...
exactly how do you settle this device of equations: displaystyle2x+y=1quad extandquad4x=-2y+6 ?
check out a solution process below:Explanation:Step 1) solve the an initial equation fordisplaystyley : displaystyle2x+y=1displaystyle2x-left(2x ight)+y=1-left(2x ight) ...
2x+y=16;x-4y=10 Solution : x,y = 74/9,-4/9 mechanism of linear Equations entered : <1> 2x + y = 16 <2> x - 4y = 10 Graphic representation of the Equations : y + 2x = 16 -4y + x = 10 solve by ...
More Items     To settle a pair that equations making use of substitution, very first solve among the equations for among the variables. Climate substitute the result for the variable in the other equation.
Choose among the equations and solve it because that x through isolating x top top the left hand side of the equal sign.
Substitute 1 because that y in x=3y-1. Because the result equation consists of only one variable, you have the right to solve for x directly.
left(eginmatrix-1&3\3&-2endmatrix ight)left(eginmatrixx\yendmatrix ight)=left(eginmatrix1\4endmatrix ight)
inverse(left(eginmatrix-1&3\3&-2endmatrix ight))left(eginmatrix-1&3\3&-2endmatrix ight)left(eginmatrixx\yendmatrix ight)=inverse(left(eginmatrix-1&3\3&-2endmatrix ight))left(eginmatrix1\4endmatrix ight)
Left multiply the equation by the inverse procession of left(eginmatrix-1&3\3&-2endmatrix ight).
left(eginmatrix1&0\0&1endmatrix ight)left(eginmatrixx\yendmatrix ight)=inverse(left(eginmatrix-1&3\3&-2endmatrix ight))left(eginmatrix1\4endmatrix ight)
left(eginmatrixx\yendmatrix ight)=inverse(left(eginmatrix-1&3\3&-2endmatrix ight))left(eginmatrix1\4endmatrix ight)
left(eginmatrixx\yendmatrix ight)=left(eginmatrixfrac-2-left(-2 ight)-3 imes 3&-frac3-left(-2 ight)-3 imes 3\-frac3-left(-2 ight)-3 imes 3&frac-1-left(-2 ight)-3 imes 3endmatrix ight)left(eginmatrix1\4endmatrix ight)
For the 2 imes 2 procession left(eginmatrixa&b\c&dendmatrix ight), the inverse procession is left(eginmatrixfracdad-bc&frac-bad-bc\frac-cad-bc&fracaad-bcendmatrix ight), therefore the procession equation can be rewritten as a matrix multiplication problem.
left(eginmatrixx\yendmatrix ight)=left(eginmatrixfrac27&frac37\frac37&frac17endmatrix ight)left(eginmatrix1\4endmatrix ight)
left(eginmatrixx\yendmatrix ight)=left(eginmatrixfrac27+frac37 imes 4\frac37+frac17 imes 4endmatrix ight)
In order to fix by elimination, coefficients of among the variables must be the exact same in both equations so the the variable will certainly cancel out when one equation is subtracted indigenous the other.
To do -x and 3x equal, multiply every terms on each side that the very first equation through 3 and all terms on every side of the second by -1.
Add -3x to 3x. State -3x and 3x release out, leaving an equation with only one change that deserve to be solved.

See more: 16000 Hours Equals How Many Days Is 16000 Hours To Days, Convert 16000 Hours To Days

Substitute 1 for y in 3x-2y=4. Since the result equation contains only one variable, you have the right to solve because that x directly.
left< eginarray together l 2 & 3 \ 5 & 4 endarray ight> left< eginarray l l l 2 & 0 & 3 \ -1 & 1 & 5 endarray ight>      EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు